Analisis Desain Boom, Arm, dan Bucket Alat Peraga Mini Excavator Zhugimada dengan Metode Elemen Hingga - Prihadianto, Braam Delfian; Darmo, Suryo; Anggoro Hasan, Dani; Nur Esa, Suhada (Infotekmesin, 2024)
An excavator is heavy equipment with a hydraulic system as the main drive and along with its uses, many parties have developed it as a means of production and as a means of learning. The education world needs excavators as learning tools and practice media are currently constrained by price when commercial units are used. Therefore, a learning media that is more compact but does not abandon the main essence of learning is needed. This research aims to analyze the front attachment design of the Zhugimada mini excavator using the finite element method. The research was carried out using the ANSYS application for the static load simulation process and testing was carried out with a bucket containing sand weighing 25 kg and using three hydraulic cylinders. The simulation results show that the maximum von Mises stress value in the bucket component is 43.226 MPa and the maximum deformation is 0,51285 mm in the tooth bucket so in general the design of the Zhugimada mini excavator front attachment components can be declared safe and can be continued in the fabrication process.